An improved power quality boost-flyback SSIPP fed BLDC motor drive. (1st January 2014) - Singh, Bhim; Bist, Vashist
This paper presents a single-stage isolated power factor corrected power supply (SSIPP) fed permanent magnet brushless DC (BLDC) motor drive. An advantage of fast voltage regulation with single voltage control loop of SSIPP is utilised to develop a power factor correction (PFC) based BLDC motor drive. The speed of BLDC motor is controlled by varying the DC link voltage of the voltage source inverter (VSI) feeding BLDC motor using a single voltage sensor. A boost-flyback SSIPP operating in discontinuous inductor current mode (DICM) is used for the voltage control with improved power quality at AC mains. A fundamental frequency switching of VSI is used instead of pulse width modulation (PWM) switching to avoid high frequency switching losses in it. The performance of the proposed BLDC motor drive is evaluated for wide range of speed control with power quality indices with-in the recommended limits of international power quality standards such as IEC 61000-3-2.